Letter : Invitation to British women to Spain - Schevenels, Walther, b. 1894
012a-0040-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe Sch/H TELEGRAMS INTERFED-PARIS TELEPHONE INVALIDES 45-88 EXECUTIVE COMMITTEE : President: W. M Citrine. Great Britain Vice-Presidents: H. Jacobsen, Denmark ; L. Jouhaux, France ; E Kupers, Holland; Corn. Mertens, Belgium; R Tayerle, Czechoslovakia General Secretary : W Schevenels AFFILIATED COUNTRIES ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INOIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA Letter F.I de Sol No.870 17th September 1938. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, INVITATION TO BRITISH WOMEN TO SPAIN In reply to your letter of the 15th September, under this heading, I regret not being able to give you the precise information you require. I do not know either of the two bodies concerned in the invitation - the Liaison Committee (Comité de Enlace) of the UGT and CNT Unions in Catalonia, and the Women's Sections of the Catalonian Iron and Steel Trade Unions - nor do I know the exact purpose of the invitation, except what is generally known about invitations to visit Spain. The Spanish comrades are very keen to have as many visitors as possible from different countries, for the purposes of propaganda, but sometimes, as you know, delegations have been exploited by those bodies in Spain which are under very strong Communist influence and used to support Communist propaganda for the international unity slogan. I do not know whether this invitation has been issued with the approval of the UGT, but I am at once asking them about it, and will write to you again as soon as I have a reply. Yours sincerely, W. Schevenels, General Secretary: 292/946/12a/40